Inter-organ Communication in the Regulation of Lipid Metabolism: Focusing on the Network Between the Liver, Intestine, and Heart - Masanori Ito; Satomi Adachi-Akahane (Elsevier, 2013)
Recent studies have shown that lipid metabolism is regulated through the orchestration of multiple organs. Gut microbiota influences the metabolism of the liver through the production of fatty acids and phosphatidylcholine as well as the modulation of bile acid profile. Microbiota also affects the cardiovascular system through the production of metabolites from nutrients. MicroRNAs (miRNAs) are non-coding RNAs comprised of around 22 nucleotides in length. MiRNAs are released into blood flow from organs and interfere with the gene expression of target organs. MiRNAs are involved in the regulation of metabolic homeostasis including lipoprotein production and cardiovascular functions. Fatty acids are also circulating and distributed to each organ by fatty acid transporting proteins. Fatty acids can act as a ligand of G protein-coupled receptors, such as GPR41 and GPR43, and nuclear receptor PPARα, which bear crucial roles in the regulation of energy expenditure. Therefore the inter-organ communication plays important roles in the systematic regulation of lipid metabolism. Studies on the inter-organ network system will contribute to the development of diagnostic and therapeutic strategies for metabolic diseases. This review discusses how lipid metabolism is regulated by the inter-organ communication, focusing on the network axis between the liver, intestine, and heart. Keywords:: inter-organ communication, lipid metabolism, liver, intestine, heart